2006
DOI: 10.1172/jci29128
|View full text |Cite
|
Sign up to set email alerts
|

Casq2 deletion causes sarcoplasmic reticulum volume increase, premature Ca2+ release, and catecholaminergic polymorphic ventricular tachycardia

Abstract: Cardiac calsequestrin (Casq2) is thought to be the key sarcoplasmic reticulum (SR) Ca 2+ storage protein essential for SR Ca 2+ release in mammalian heart. Human CASQ2 mutations are associated with catecholaminergic ventricular tachycardia. However, homozygous mutation carriers presumably lacking functional Casq2 display surprisingly normal cardiac contractility. Here we show that Casq2-null mice are viable and display normal SR Ca 2+ release and contractile function under basal conditions. The mice exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
532
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(579 citation statements)
references
References 55 publications
42
532
5
Order By: Relevance
“…Knollmann and coworkers showed that Casq2-null mice are viable and display normal SR Ca 2þ release and contractile function under basal conditions. However, exposure to catecholamines in Casq2-null myocytes caused increased diastolic SR Ca 2þ leak, resulting in premature spontaneous SR Ca 2þ releases that triggered beats indicating that these mice are susceptible to catecholaminergic ventricular arrhythmias (Knollmann et al 2006). FKBPs are named according to their molecular mass and belong to the immunophilins, a family of highly conserved proteins that bind immunosuppressive drugs such as FK506 and rapamycin.…”
Section: Calsequestrinmentioning
confidence: 99%
“…Knollmann and coworkers showed that Casq2-null mice are viable and display normal SR Ca 2þ release and contractile function under basal conditions. However, exposure to catecholamines in Casq2-null myocytes caused increased diastolic SR Ca 2þ leak, resulting in premature spontaneous SR Ca 2þ releases that triggered beats indicating that these mice are susceptible to catecholaminergic ventricular arrhythmias (Knollmann et al 2006). FKBPs are named according to their molecular mass and belong to the immunophilins, a family of highly conserved proteins that bind immunosuppressive drugs such as FK506 and rapamycin.…”
Section: Calsequestrinmentioning
confidence: 99%
“…Ventricular myocytes from 12-to 16-week-old mice (C57BL/6 strain) were isolated using modified collagenase/protease method, as previously described [16]. All chemicals, unless otherwise specified, were obtained from Sigma (St. Louis, MO).…”
Section: Myocyte Isolation and Ca 2+ Indicator Loadingmentioning
confidence: 99%
“…Cardiomyocytes were inoculated in 35 mm dishes (MatTeK Corporation, USA) and loaded with 5 μM fluo-3 AM (Sigma Chemical Co., USA). Intracellular fluo-3 AM was excited by a DG-4 quartz lamp filtered at 488 nm, and emission wavelengths were monitored with a 520 nm long-pass filter in 37 °C perfusion solution (in mM: 145 NaCl, 5.4 KCl, 0.5 MgCl 2 , 1.2 CaCl 2 , 5 HEPES, 5.5 Glucose, 0.3 NaH 2 PO 4 , pH 7.4) [20]. Rapid scanning of the observation field (5 s/scan) was used to minimize photo-oxidation artifacts.…”
Section: 25mentioning
confidence: 99%